Dentine hypersensitivity: analysis of self-care products - Cassiano Kuchenbecker Rösing; Tiago Fiorini; Diego Nique Liberman; Juliano Cavagni (Sociedade Brasileira de Pesquisa Odontológica, 2009)
Dentine hypersensitivity is a condition that is often present in individuals, leading them to seek dental treatment. It has been described as an acute, provoked pain that is not attributable to other dental problems. Its actual prevalence is unknown, but it is interpreted as very unpleasant by individuals. Several therapeutic alternatives are available to manage dentine hypersensitivity, involving both in-office treatment and home-use products. The aim of this literature review was to evaluate self-care products for managing dentine hypersensitivity. Among the products available, dentifrices and fluorides are the most studied self-care products, with positive effects. However, a high percentage of individuals is affected by the placebo effect. Among dentifrices, those containing potassium salts seem to be the most promising. Dental professionals need to understand the advantages and limitations of these therapies and use this knowledge in a positive approach that might help in decreasing dentine hypersensitivity among patients.